Tradisi Pernikahan Kerubahan Gunung Perspektif Fenomenologi - Sulton Muzadi; Muhammad Solikhudin (Lembaga Penelitian, Penerbitan dan Pengabdian kepada Masyarakat (LP3M) IAIFA Kediri, 2022)
People's views on the value of marriage are considered sacred in life, and Islam upholds a marriage. When a person has fulfilled the requirements of the pillars of marriage, he immediately entered into a marriage contract, because it would be dangerous to delay marriage. However, in Candisari Village, Sambeng District, Lamongan Regency, the phenomenon of the